Novos suportes, antigos temores: tecnologia e confrontode gerações nas práticas de leitura e escrita - Solange Jobim e Souza; Nilton Gamba Jr (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2002)
The paper analyses contemporary production of knowledge about the act of reading and writing, as well as the social, political and cultural conditionings that have led to changes in it. We focus on two aspects related to the issue: the impact of the supporting materials that have changed ways of reading and writing throughout time; and the challenges imposed on the dialogue between generations, brought about by the electronic revolution. We revisit concepts developed by Mikhail Bakhtin, casting new lights upon the present uses of language and text production mediated by electronic and digital supporting materials.